Stable routing algorithm for mobile ad hoc networks using mobile agent. (16th April 2012) - Varaprasad, G.
SUMMARY Wireless ad hoc networks are growing important because of their mobility, versatility, and ability to work with fewer infrastructures. The mobile ad hoc network is an autonomous system consisting of mobile nodes connected with wireless links. Establishing a path between two nodes is a complex task in wireless networks. It is still more complex in the wireless mobile ad hoc network because every node is no longer as an end node and an intermediate node. In this paper, it focuses on design of connectionless routing protocol for the wireless ad hoc networks based on the mobile agent concept. The proposed model tries to discover the best path taking into consideration some concerns like bandwidth, reliability, and congestion of the link. The proposed model has been simulated and tested under various wireless ad hoc network environments with the help of a different number of nodes. The results demonstrate that the proposed model is more feasible for providing reliable paths between the source and destination with the minimum control message packets over the network. It has delivered more number of packets to the destination over the network. Copyright © 2012 John Wiley & Sons, Ltd.